(untitled) (Research, Society and Development, 2025)
Open book pelvic trauma represents a severe and potentially fatal condition in orthopedic emergencies, often associated with hemodynamic instability and high mortality rates. Prompt diagnosis and appropriate emergency management are critical determinants of patient survival. The aim of this study was to conduct a systematic review of the literature to identify and synthesize available evidence regarding the diagnosis and initial management of open book pelvic injuries. Searches were performed in PubMed, Scopus, Web of Science, Embase, and Cochrane databases using descriptors related to “pelvic fracture”, “open book injury”, “emergency orthopedics”, “management”, and “resuscitation”. Studies published between 2005 and 2025, in English, Portuguese, and Spanish, were considered. After screening, the included studies indicated that early diagnosis combined with immediate stabilization using external devices (such as pelvic binders) and effective hemorrhage control (arterial embolization or surgery) are key factors for improving clinical outcomes. Despite advances, protocol heterogeneity and the lack of large-scale randomized clinical trials limit standardization of management.